PERENCANAAN KEUANGAN SYARIAH DALAM UPAYA MENINGKATKAN KEMAMPUAN MANAJEMEN KEUANGAN BAGI PARA IBU RUMAH TANGGA KEC. CITAMIANG KOTA SUKABUMI - Anggriani, Reni; Sofiani, Venita (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2024)
There have been many studies that discuss Islamic financial planning for families. However, research that discusses Islamic financial planning to improve Islamic financial management and Islamic investment is still limited. This research was carried out to continue the service that has been carried out to housewives in Citamiang District, Sukabumi City. The background of this research is to find out how successful housewives are in understanding and managing financial planning in sharia so that they can improve their ability in sharia financial management and invest in sharia investments. This research method uses qualitative descriptive, by collecting questionnaire data to 50 housewives in Citamiang District, Sukabumi City, observation and documentation study. The results of the study show that housewives have done a good record of their income and expenses, do financial planning by determining the most important main needs, and prefer easy investments without having to take a period of time.